Polymerase chain reaction optimization for the detection of Pasteurella multocida B:2, the causative agent of Haemorrhagic septicaemia - Lily Natalia; Adin Priadi (Indonesian Center for Animal Research and Development (ICARD), 2001)
Specific detection of Pasteurella multocida type B:2 by polymerase chain reaction (PCR), using a set of DNA primers wasoptimised. Effects of the addition of ethylene diamine tetra acetic acid (EDTA) to the sample preparation, Escherichia coli contamination and the number of P. multocida on the PCR product was assessed. The PCR test was compared to the standard bacteriological method for the detection of P. multocida B:2 in tonsillar swab samples collected from slaughter houses of various regions in Indonesia. Addition of 100 mM EDTA-saline to P. multocida B:2 spiked tonsillar swab samples inhibits the production 350 base pairs (bp) PCR product. The inhibitory effect of the EDT A can be eliminated by three times washing with deionised water. The PCR can detect P. multocida as low as I organism and contanimation of 100 CFU of E. coli does not effect the PCR result. The results show that the DNA primers for P. multocida B:2 is sensitive and specific. The inhibitory effect of EDTA in PCR samples can be eliminated by washings. Keywords: PCR, EDT A, Pasteurella multocida B:2